Practical Success of Biomanipulation using Filter-Feeding Fish to Control Cyanobacteria Blooms: A Synthesis of Decades of Research and Application in a Subtropical Hypereutrophic Lake - Ping Xie; Jiankang Liu (The Scientific World Journal)
337 Lake Donghu is a 32-km 2 shallow, subtropical lake near the Yangtze River (P.R. China) that has experienced dramatic changes in the past five decades. These changes include: (1) a trophic state change from mesotrophy to hypertrophy; (2) dense blooms of cyanobacteria during every summer from the 1970s to 1984; (3) a cessation of blooms starting in 1985, with no recurrence; and (4) an increase, coincident with bloom declines, in the production of silver and bighead carp (filter-feeders) by more than tenfold. There are several possible explanations for the disappearance of blooms, including changes in nutrient concentrations, increased zooplankton grazing, and increased grazing on algae by fish. The long-term data suggest that changes in nutrients or in zooplankton were not important, but that the remarkably increased fish densities might have played the key role. To test this hypothesis, in situ enclosure experiments were conducted in three years. The main conclusions are as follows: (1) an increased stocking of the lake with carp played a decisive role in the elimination of cyanobacteria blooms; (2) both silver and bighead carp can eliminate cyanobacteria blooms directly by grazing; (3) zooplankton cannot suppress the blooms; and (4) the lake still is vulnerable to the outbreak of blooms, should fish grazing decline. The critical biomass of carp is approximately 50 g m 3 . The results suggest the applicability of a new food-web manipulation (increased stocking with filter-feeding fish) for controlling cyanobacteria blooms in hypereutrophic lakes. The approach differs from traditional biomanipulation in Europe and North America, where piscivores are added to control planktivores, and this in turn increases zooplankton and decreases algae. The new biomanipulation method is being used or being tested to counteract cyanobacteria blooms in many Chinese lakes such as Lake Dianchi?Xie and Liu: Biomanipulation to Control Cyanobacteria TheScientificWorld (2001) 1, 337-356 in Yunnan Province, Lake Chaohu in Anhui Province, and Lake Taihu in Jiangsu Province. The method has great potential as an important component of an integrated approach to counteract cyanobacteria blooms, especially in lakes where nutrient inputs cannot be reduced sufficiently, and where zooplankton cannot effectively control phytoplankton production.